A Study on Consumer Perception towards Indigenous Toy Market of UP with special reference to Kanpur (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Consumer perception of the indigenous toy market in Uttar Pradesh is generally positive, with a willingness to support local artisans and a strong appreciation for the cultural and traditional aspects of these toys. However, there are concerns about quality, price, and accessibility that should be addressed to further boost the growth of this market. This analysis underscores the potential for indigenous toys to play a significant role in preserving cultural heritage and supporting local economies, but it also highlights the need for strategic efforts to strengthen and expand this industry.